2008
DOI: 10.17221/424-pse
|View full text |Cite
|
Sign up to set email alerts
|

Direct and subsequent effect of compost and poultry manure on the bioavailability of cadmium and copper and their uptake by oat biomass

Abstract: Direct and subsequent influence of added organic materials on changes of cadmium and copper bioavailability in soil and their accumulation in aboveground oat (Avena sativa L.) biomass was studied in a three-year experiment. Mineral NPK, poultry manure and two types of composts were used as fertilizers. The average portion of available cadmium and copper from their total content in soil in all treatments was 0.94% and 0.25%, respectively. After application of poultry manure the concentration of available Cd inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…In our previous studies, we tested the effect of lime, limestone, bentonite and zeolite as ameliorative materials (Hanc et al, 2006), and the effect on Cd mobility of poultry manure and composts as organic materials (Hanc et al, 2008). One of the most effective stabilizers found was compost.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we tested the effect of lime, limestone, bentonite and zeolite as ameliorative materials (Hanc et al, 2006), and the effect on Cd mobility of poultry manure and composts as organic materials (Hanc et al, 2008). One of the most effective stabilizers found was compost.…”
Section: Introductionmentioning
confidence: 99%
“…This, in a way, can reduce the source of contaminant and subsequent transfer of heavy metal to edible portion of Corchorus. Previous studies have reported that the origin of a particular compost material could be a potential source of heavy metals in the plant tissues (Petersen et al 2003;Hanč et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Composted organic manure especially from poultry wastes have been reported to improve mineral composition in tissues of vegetables such as Jute mallow (Mazen et al 2010;Jonathan et al 2012). In contrast to the beneficial roles of compost, it could also be a potential source of contaminants depending on its origin (Petersen et al 2003;Hanč et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For the mobilization, metals are released into the soil and subsequently removed through native plant species. The application of poultry manure increased the available Cd concentration in soil and Cd uptake by Avena sativa L. proportionally during a 3-year experiment (Hanč et al 2008). According to Meeinkuirt et al (2013), the application of cow manure and organic fertilizer in the pot experiment and Osmocote® in the field experiment resulted in an increase of Pb uptake in both phytostabilization grass species of Thysanolaena maxima and Vetiveria zizanioides.…”
Section: Introductionmentioning
confidence: 99%